Grant of Sucrose and Non-Nutritive Sucking to Pain Response and the Long Cries of Neonates to Invasive Procedures - Kristiawati Kristiawati; Krisna Yetti; Hening Pujasari (Universitas Airlangga, 2010)
Intoduction: Hospitalized neonates may experience pain caused by invasive procedures. Sucrose and non-nutritive sucking are non-pharmacological analgesics. The aimed of this study was to examine the effectiveness of sucrose and non-nutritive sucking administration on pain and crying duration of neonates during invasive procedures.Method: The study used quasi-experimental design with post-test only control group design approach. This study used nonprobability sampling technic with consecutive sampling. The sample consisted of 45 neonates, divided into three groups, each group of 15 neonates.Result: The results showed that the pain response and the crying duration were insignificantly different between the sucrose group and the NNS, respectively p = 0.635 and p = 0.848.Discussion: Age was identified as a confounding variable that effected pain responses. Provision of sucrose and NNS proven to reduce pain as non-pharmacological pain management for neonates during invasive procedures.